2019
DOI: 10.2147/copd.s187560
|View full text |Cite|
|
Sign up to set email alerts
|

<p>Ultrafine particles in airways: a novel marker of COPD exacerbation risk and inflammatory status</p>

Abstract: Purpose Ultrafine particles (UFP) are toxic due to their small size and penetration into deeper lung compartments. We aimed to evaluate the exhaled breath condensate (EBC)-UFP content as a reflection of inflammation and oxidative stress status in COPD patients and as an exacerbation risk marker. Methods EBC was collected by conventional methods. Particles were analyzed with NanoSight LM20. EBC carbonyl and 8-hydroxydeoxyguanosine (8-OHdG) levels were measured using ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 38 publications
1
22
1
Order By: Relevance
“…A portable condenser (TURBODECCS, ItalChill, Parma, Italy) was used as described in detail elsewhere [ 14 ]. Briefly, subjects breathed into a collecting system for 5 min at normal tidal volume.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A portable condenser (TURBODECCS, ItalChill, Parma, Italy) was used as described in detail elsewhere [ 14 ]. Briefly, subjects breathed into a collecting system for 5 min at normal tidal volume.…”
Section: Methodsmentioning
confidence: 99%
“…The size and concentration of the particles was assessed in EBC and serum samples with the NanoSight LM20 system (NanoSight Ltd., Salisbury, UK) [ 14 ]. Briefly, the Brownian motion of particles in the range of 10–1000 nm was captured by the camera.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…After reading these studies, eight were included into the narrative description and six into quantitative synthesis. The study by (Fireman Klein et al 2019) was excluded because only the arithmetic mean was reported -no variability (SD GSD, IC IQR) indicated. The control group in (Pelclova et al 2016b) and in (Pelclova et al 2016c) was identical and was therefore not included twice.…”
Section: Study Selectionmentioning
confidence: 99%